Effects of intrauterine exposure to concentrated ambient particles on allergic sensitization in juvenile mice. (November 2021) - de Brito, Jôse Mára; de Ameida, Francine Maria; Arantes-Costa, Fernanda Magalhães; Guimarães, Eliane Tigre; Morgan, Adriana; Mangone, Flavia Rotea; Pavanelli, Ana Carolina; Nagai, Maria Aparecida; Vieira, Rodolfo P.; Macchione, Mariângela; Mauad, Thais
Graphical abstract: Effects in the experimental CAPs, HDM and CAPs+HDM groups in relation to the control (FA) group Highlights: PM2.5 prenatal exposure did not increase allergic inflammation in juvenile mice. PM2.5 intrauterine exposure altered the immune profile of juvenile mice. The exposure showed lower levels of IL-4, TNF-α, and IL-2, which differed by sex. The decreased cytokine profile could imply altered responses to infections. Abstract: Intrauterine exposure to particulate matter (PM) has been associated with an increased risk of asthma development, which may differ by the age of asthma onset, sex, and pollutant concentration. To investigate the pulmonary effects of in utero exposure to concentrated urban ambient particles (CAPs) in response to house dust mite (HDM) sensitization in juvenile mice. Mice were exposed to CAPs (600 μg/m 3 PM2.5 ) during the gestational period. Twenty-two-day postnatal mice were sensitized with HDM (100 μg, intranasally, 3 times per week). Airway responsiveness (AHR), serum immunoglobulin, and lung inflammation were assessed after 43 days of the postnatal period. Female (n = 47) and male (n = 43) mice were divided into four groups as follows: (1) FA : not exposed to CAPs; (2) CAPs : exposed to CAPs; (3) HDM : sensitized to HDM; and (4) CAPs+HDM : exposed to CAPs and HDM-sensitized. PM2.5 exposure did not worsen lung hyperresponsiveness or allergic inflammation in sensitized animals. The levels of the lung cytokines IL-4, TNF-α, and IL-2 were differentially altered in male and female animals. Males presented hyporesponsiveness and increased lung macrophagic inflammation. There were no epigenetic changes in the IL-4 gene. In conclusion, intrauterine exposure ambient PM2.5 did not worsened allergic pulmonary susceptibility but affected the pulmonary immune profile and lung function, which differed by sex.